The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.29303/lisdaya.v17i2.42
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Self-Directed Learning in English Foreign Language Classes During the Covid-19 Pandemic

Abstract: The success of learning cannot be separated from the level of self-directed learning (SDL) of the students. Therefore, this study aims at describing the level of EFL learners’ self-directed learning and exploring the main factors which affect their SDL levels. The method used in this study is descriptive qualitative research. The participants are the fourth-semester students of the English Education Program in higher education in Lombok. The data were collected by using two sets of questionnaires: a close-ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…First, the findings revealed that the EFL students felt that the support of their families was the highest level of social support they have received; thus played a significant role in their academic success. Such finding corresponds with (Ashadi et al, 2022;Aghayani and Janfeshan, 2020;Dewi, Marlina and Supriyono, 2019;Du Toit-Brits, 2018;Dwilestari, 2021;Murniati, Hartono, and Nugroho, 2023) who found that EFL students who received social support from family members or teachers at schools exhibited high level of SDL. This type of support allow EFL students to interlink with their family members, teachers, society, and environment; thus, help the EFL shape their SDL experience, and understand the process to use acquired skills for lifetime learning.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, the findings revealed that the EFL students felt that the support of their families was the highest level of social support they have received; thus played a significant role in their academic success. Such finding corresponds with (Ashadi et al, 2022;Aghayani and Janfeshan, 2020;Dewi, Marlina and Supriyono, 2019;Du Toit-Brits, 2018;Dwilestari, 2021;Murniati, Hartono, and Nugroho, 2023) who found that EFL students who received social support from family members or teachers at schools exhibited high level of SDL. This type of support allow EFL students to interlink with their family members, teachers, society, and environment; thus, help the EFL shape their SDL experience, and understand the process to use acquired skills for lifetime learning.…”
Section: Discussionsupporting
confidence: 77%
“…Besides, it revealed that the efficient segment of teachers' assistance is a crucial factor in enhancing students' self-regulation skills against the backdrop of disorganization in the conventional training system. Likewise, Dwilestari (2021) explored the overlap of the challenges and opportunities in schools by testing the implications of SDL in the context of English as a foreign language class during the pandemic. The study described flexible learning techniques and social companions as the most important factors for the success of classroom transformation.…”
Section: Theoretical Background and Related Studiesmentioning
confidence: 99%
“…Some students who live in rural areas admit to having difficulties due to poor internet connections and not being used to the implementation of ICT-based learning. This statement is supported by a study by Dwilestari, (2021) which states that in these situations, it will clearly make a big difference in the field of education. One of the common challenges that students faced via online learning is poor internet connection.…”
Section: Introductionmentioning
confidence: 81%
“…Students' self-directed learning in English (foreign language) [56], Challenges and opportunities in online distance learning [57], Digital engagement and academic functioning [58], and Effects of the COVID-19 pandemic on k-12 education [59] are the topics of the articles considering two of the three variables to be positive and one of them negative (see Table 1). For the articles that looked at student's self-directed learning in English when studied as a foreign language, and the one concerned with the effects of the COVID-19 pandemic on K-12 education, both self-directed learning and mental health were found to be positive while online learning had a negative effect on the students.…”
Section: Two Positive One Negativementioning
confidence: 99%